The Effect of Progressive Muscle Relaxation on Depression and Blood Glucose Levels in Patients with Type 2 Diabetes Mellitus - Hikni Rahmat Fauji; Rahayu Setyowati; Rina Nuraeni; Hera Hijriani (Jurnal Kesehatan Budi Luhur: Jurnal Ilmu-Ilmu Kesehatan Masyarakat, Keperawatan, dan Kebidanan, 2026)
Type 2 Diabetes Mellitus (T2DM) is a chronic metabolic disease that is often accompanied by psychological disorders, particularly depression, which may adversely affect glycemic control and quality of life. Progressive Muscle Relaxation (PMR) is a complementary non-pharmacological intervention with the potential to improve both psychological and physiological outcomes in patients with T2DM. This study aimed to determine the effect of Progressive Muscle Relaxation on depression and blood glucose levels in patients with Type 2 Diabetes Mellitus. A pre-experimental study using a one-group pretest-posttest design was conducted at the Internal Medicine Polyclinic of Majalengka Regional Hospital in 2026. A total of 35 patients with Type 2 Diabetes Mellitus were selected using purposive sampling. Depression was measured using the Beck Depression Inventory-II (BDI-II), while blood glucose levels were assessed using random blood glucose testing. Data were analyzed using the paired-samples t-test and the Wilcoxon signed-rank test, with a significance level of p < 0.05. The mean depression score decreased from 18.43 to 16.80, while the mean random blood glucose level decreased from 231.89 mg/dL to 190.26 mg/dL after the intervention. Statistical analysis showed that Progressive Muscle Relaxation significantly reduced depression (p < 0.001) and random blood glucose levels (p = 0.002). Progressive Muscle Relaxation was associated with improvements in depression scores and random blood glucose levels among patients with Type 2 Diabetes Mellitus. PMR may serve as a complementary nursing intervention to support comprehensive diabetes management.